Investigation of Indoor Environment Conditions in Low-Rise Condominiums in Bangkok - Chaloeytoy, Kittiwoot; Khumpairoj, Thanyatorn; Sikram, Tanadej; Ichinose, Masayuki; Alkhalaf, Haitham (Journal of Advanced Research Design, 2025)
Indoor Environmental Quality is critical for ensuring residents’ comfort and health, particularly in residential buildings. However, currently there is a significant research gap in IEQ studies for low-rise urban condos, which are likely to suffer from worse conditions due to external pollution and the urban heat island effect than high rise condos. This study seeks to address this lack by performing field assessments and deploying questionnaires to ascertain the state of IEQ and its impact on the inhabitants. The results reveal that the external pollution sources, along with concerns for safety and insects, influence behaviors such as keeping windows closed. This behavior has a detrimental effect on indoor air quality. Measurements of noise and CO2 levels within these buildings frequently surpassed acceptable thresholds, corroborating the findings from occupant satisfaction surveys. While other IEQ parameters like room temperature, relative humidity, and lighting largely met established standards and garnered satisfaction.